PENGARUH DOSIS ARANG AKTIF TERHADAP PERKECAMBAHAN EMBRIO SOMATIK KEDELAI (Glycine max L.) - Gustian, Gustian; Swasti, Etti; Tori, Nandita Samaralya; Sari, Silvia Permata (Agros Journal of Agriculture Science, 2023)
Soybeans (Glycine max L.) are a type of leguminous food crop that is important as a source of protein and vegetable oil, making them a good potential for human growth. Efforts that can be made to increase production and productivity while reducing imports and soybean development include the assembly of superior varieties through tissue culture, with regeneration through somatic embryogenesis. Somatic embryos that have been produced are matured to obtain seedlings by adding activated charcoal. This research aims to determine the effect and the appropriate dosage of activated charcoal for the germination of somatic embryos of soybeans. The research was conducted in the Tissue Culture Laboratory of the Faculty of Agriculture, Andalas University, Padang, from May to August 2023. The research was arranged in a completely randomized design (CRD) with five treatment levels of activated charcoal dosage, namely 1, 1.5, 2, 2.5, and 3 g/l. The data were analyzed using a 5% level F test, and if the calculated F was greater than the Pr(>F), it was followed by a post hoc test using Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results of the research show that the addition of activated charcoal to the media can germinate somatic embryos of soybean plants. In the media containing 2 g/l of activated charcoal, seedlings emerged at 27.15 days after sowing (DAS), and 96.67% of somatic embryos germinated.  Keywords: Activated charcoal, germination, somatic embryo, soybean INTISARIKedelai (Glycine max L.) merupakan tanaman pangan jenis polong polongan yang penting sebagai sumber protein dan minyak nabati, sehingga memiliki potensial yang baik untuk pertumbuhan tubuh manusia. Upaya yang dapat dilakukan untuk meningkatkan produksi dan produktivitas dalam menekan jumlah impor dan pengengembangan kedelai yaitu dengan perakitan varietas unggul melalui kultur jaringan yang regenerasinya melalui embriogenesis somatik. Embrio somatik yang telah dihasilkan dilakukan maturasi untuk mendapatkan kecambah dengan metode penambahan arang aktif. Penelitian ini bertujuan untuk mengetahui pengaruh dan dosis arang aktif yang tepat untuk perkecambahan embrio somatik kedelai. Penelitian dilaksanakan di Laboratorium Kultur Jaringan Fakultas Pertanian Universitas Andalas Padang, pada Mei sampau Agustus 2023. Penelitian disususn dalam Rancangan acak lengkap (RAL) dengan 5 taraf perlakukan dengan dosis arang aktif 1, 1,5, 2, 2,5, dan 3 g/l. Data dianalisis menggunakan uji F taraf 5%, jika F hitung lebih besar dari Pr(>F) maka dilanjutkan dengan uji lanjut dengan menggunakan Duncan Multipel Range Test (DMRT) pada taraf 5%. Hasil penelitian menunjukan bahwa pemberian arang aktif pada media dapat mengecambakan embrio somatik tanaman kedelai. Pada media yang mengandung 2 g/l arang aktif menunjukan waktu muncul kecambah pada 27,15 HST dan 96,67% embrio somatik berkecambah. Kata Kunci: Arang aktif, perkecambahan, embrio somatik, kedelai